Analysis of infant cry through weighted linear prediction cepstral coefficients and probabilistic neural network - Hariharan, Muthusamy; Lim, Sin Chee; Sazali, Yaacob, Prof. Dr. (Springer Science+Business Media, LLC., 2012)
Link to publisher's homepage at http://www.springerlink.com/